Designing Cellulose Acetate - Polyacrylamide Semi-Interpenetrating Polymer Networks and Evaluation of their Protein Retention Behavior. Issue 5 (24th March 2019) - Shukla, Pallavi; Bajpai, Anil Kumar; Bajpai, Rakesh
ABSTRACT: In this work semi-IPNs of cellulose acetate (CA) – N, N'- methylene bisacrylamide (MBA) – crosslinked polyacrylamide (PAM), and native CA gel were prepared and characterized by FTIR, AFM, SEM, XRD, TGA and DSC techniques. The AFM studies revealed that addition of AM increased the symmetry of the semi-IPN surfaces whereas the XRD spectra suggested for a decrease in crystalline nature of CA. The network parameters were changed with change in concentrations of CA and AM. The prepared semi-IPNs were examined for retention of bovine serum albumin (BSA). The mechanical properties, swelling capacity, % porosity and biocompatibility were also investigated. Graphical Abstract: